Knowledge and practice of family planning in married women of reproductive age group in a slum of Kolkata - Santanu Ghosh; Amrita Samanta; Shuvankar Mukherjee (Al Ameen Medical College, 2013)
Background: The roots of the factors influencing family planning issues are entrenched in the socio- cultural milieu of Indian society. Objectives: To determine knowledge and practice of contraception, to find out association, between contraceptive practices and different socio-demographic variables and to elicit factors behind lack of contraception. Methodology: A cross-sectional, community based study was conducted among 352 women of 15-49 year age group of urban field service area, Kasba of Calcutta National Medical College, Kolkata using a pretested and predesigned schedule. Results: Only 9% had no idea about contraception. Family members were the major source of knowledge (39.8%) followed by TV (38%). Oral contraceptives pills (52.6%) was the most commonly used contraceptive followed by condom (24. 6%). About 2/3rd of the study population was currently using no contraceptive methods. The percentage of non users is more in case of per capita family income of Rs <1000/- (p<0.05) and male sex of the last child (p<0.05). Common reasons for not using any method were desire of a child (42.0%), amenorrhoea since last delivery (26.1%) and lack of motivation (20.2%). Most of the couples (53.5%) themselves made decisions on contraception though role of mother-in-laws (6.8%) was not negligible. Conclusion: There is a huge knowledge-practice gap. Mother-in-laws and husbands should be the special target groups for IEC.